Ancient Cities and Fortresses of Northern Bactria - Saypulla N. Tursunov; Ikromjon I. Umarov; Islam M. Karshiev (Археология евразийских степей, 2025)
Ancient Bactria held a significant place in the history of the peoples of Central Asia, Afghanistan, and India. This country encompassed the southern parts of Uzbekistan and Tajikistan, as well as the northern regions of Afghanistan. During the ancient Bactrian period, a unique culture emerged and developed as a result of the blending of different peoples' cultures, languages, and religions. Archaeological studies have shown that during the Bronze Age, agricultural oases arose in the territory of Northern Bactria. The inhabitants of these oases practiced irrigated farming, animal husbandry, and crafts. It was here that an early urban civilization, known as the Sapalli culture, developed. This culture is chronologically divided into the Sapalli, Jarkoton, Kuzali, Molali, and Bustan phases—each named after agricultural settlements located in specific areas. During the Early Iron Age, there were eight agricultural oases in the Surxon River valley. These oases gave rise to cities such as Jondavlattepa, Kuchuktepa, Beshkutan, Tallashkan, Bandyhan, Boyrochi, and Kyzyltepa, which were surrounded by defensive walls and fortifications. The cities of Northern Bactria served not only as strongholds but also as major economic and cultural centers. Throughout its existence, Bactria was first conquered by the Achaemenids, then by the Greco-Macedonians, and later by the Kushans. Despite this, life in Bactrian cities did not cease. Over time, the cities adapted to new conditions and continued to develop. This paper presents information about the ancient cities and settlements of Northern Bactria based on written and archaeological sources.